Finansowanie a autonomia decyzyjna przedsiębiorstwa - Różański, Jerzy (The Financing and The Enterprise Decision Autonomy, 2008)
The article qualifies the influence, which is exerted by different kinds of the enterprise financing, on making decisions in the enterprise, especially in the investment sphere. It also qualifies, how much investors' authorities affect the enterprise development chance, which methods of the financing can restrict the enterprise decision autonomy and in what method and what relations (and what result for the enterprise) arise between each investors groups and the management-team depending on the financing methods, including the conclusions from the principal-agent theory and the theory о informational asymmetry.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 490-496